Pengembangan E-Modul Interaktif Instalasi Penerangan Listrik di Pendidikan Vokasi - Al Hikmah Fajar; Taali Taali; Riki Mukhaiyar; Syaiful Islami (Jurnal Pendidikan Teknik Elektro, 2023)
This study aims to develop and produce valid and practical interactive e-modules for Class XII Electrical Lighting Installation subjects at SMK Negeri 2 Lubuk Basung. The model in this study is the 4D model with steps namely Define, Design, Development, and Dissemination. The validity test of the e-module product was carried out by 2 validators from lecturers and 1 education teacher. Media practicality test refers to the response of teachers and students. The research instrument was a media validation questionnaire and a practicality questionnaire. Based on the validation assessment by the e-module media validator, a very valid value was obtained. The practicality test by 1 subject teacher obtained a very practical value and the student practicality assessment of 25 students obtained a very practical value. Based on these results, the interactive e-module in the subject of Electrical Lighting Installation is practical and appropriate for teachers and students to use in the learning process.